Capitalism, corporations and the social contract: a critique of stakeholder theory - Mansell, Samuel F. (Business, value creation and society, 2013)
"In whose interests should a corporation be run? Over the last thirty years the field of 'stakeholder theory' has proposed a distinctive answer: a corporation should be run in the interests of all its primary stakeholders - including employees, customers, suppliers and financiers - without contradicting the ethical principles on which capitalism stands. This book offers a critique of this central claim. It argues that by applying the political concept of a 'social contract' to the corporation, stakeholder theory in fact undermines the principles on which a market economy is based. The argument builds upon an extensive review of the stakeholder literature and an analysis of its philosophical foundations, particularly concerning the social contract tradition of John Rawls and his predecessors. The book concludes by offering a qualified version of Milton Friedman's shareholder theory as a more justifiable account of the purpose of a corporation"--